Conflict, Heritage and World-Making in the Chaco : War at the End of the Worlds?. - Breithoff, Esther (UCL Press, 2020)
Conflict, Heritage and World-Making in the Chaco explores the physical remains of the Chaco War (1932-35) - known as South America's first 'modern' armed conflict - in what is now present-day Paraguay. It shows how the material culture and heritage of modern conflict fuse together objects, people and landscapes, connecting them physically and conceptually across vast distances and time periods.